Correlation of Pap smear and colposcopic findings in relation to histopathological findings among women attending a tertiary care hospital: a two year study - Gandavaram, Jyothi; Pamulapati, Bindu Reddy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cervical malignancy is ranked second among the malignancies in females with breast carcinoma the first. Screening for cervical cancer by conventional cytology and supported by colposcopy and histopathology can easily identify the premalignant lesions and also other non-invasive inflammatory lesions of the cervix. Objective of this study was to find the correlation of Pap smear, colposcopic findings and colposcopic guide biopsy in evaluation of cervical lesions in women and to analyze the various risk factors Methods: A prospective study for two years was conducted by department of obstetrics among women aged from 20-60 years. Socio demographic data, clinical history and examination were done and findings noted. Pap smear, colposcopy and colposcopic guided biopsy was done and findings were noted and analyzed foe sensitivity, specificity and compared with Pap smear. Results: In present study sensitivity of Pap smear for detecting lesions above LSIL was 28%, specificity 99.32%, PPV was 93.47%, negative predictive value 76.21% and accuracy of Pap smear was 78%. The sensitivity of colposcopy in detection of low grade lesions and above came out to be 80.2%, specificity 82.14%, positive predictive value 66.78%, negative predictive value 86.78% and accuracy of colposcopy was 84.65%.The incidence of preinvasive lesions (LSIL and HSIL) was 33.6% with LSIL (19.2%) and HSIL (14.4%) and of invasive lesions was 9.6%. Conclusions: This study suggests that accuracy of detection of cervical abnormalities is higher when cytology, colposcopic biopsy and colposcopy are used complimentarily in diagnosis of cervical lesions. Colposcopy eliminates the need for repeated follow up as in Pap smear which has low sensitivity.